2021
DOI: 10.1007/s00125-021-05463-x
|View full text |Cite
|
Sign up to set email alerts
|

A UK nationwide study of people with type 1 diabetes admitted to hospital with COVID-19 infection

Abstract: Aims/hypothesis The aim of this work was to describe the clinical characteristics of adults with type 1 diabetes admitted to hospital and the risk factors associated with severe coronavirus disease-2019 (COVID-19) in the UK. Methods A retrospective cohort study was performed using data collected through a nationwide audit of people admitted to hospital with diabetes and COVID-19, conducted by the Association of British Clinical Diabetologists from March to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…Previous studies from different countries reported the hospitalization rates in patients with T1DM between 21.9% and 51%. Also, almost one-third of our patients were admitted to the ICU, which was recorded as 5% to 35% in other studies from different countries [17,22,25,26]. In the CORONADO study, 19.6% of patients with T1DM required mechanical ventilation [23].…”
Section: Original Papermentioning
confidence: 75%
See 1 more Smart Citation
“…Previous studies from different countries reported the hospitalization rates in patients with T1DM between 21.9% and 51%. Also, almost one-third of our patients were admitted to the ICU, which was recorded as 5% to 35% in other studies from different countries [17,22,25,26]. In the CORONADO study, 19.6% of patients with T1DM required mechanical ventilation [23].…”
Section: Original Papermentioning
confidence: 75%
“…A whole-population study from England reported a 3.5% death rate among T1DM patients [16,20]. The rate of mortality in the CORONADO study was 5.4% [23], while a recent UK study reported a 27% death rate in COVID-19 patients [22]. A multicentre and another small-scale study from the United States reported 9% and 3% death rates, respectively [17,18].…”
Section: Original Papermentioning
confidence: 97%
“…A number of studies have suggested an association of co-morbidities with the COVID-19 infection [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…The data on type 1 diabetes specifically are far more limited. A UK nationwide study by Ruan et al [12], which aimed to assess the clinical characteristics and risk factors of adults with both COVID-19 and type 1 diabetes, reported 53 deaths among 194 analysed patients, constituting a mortality rate of 27.32%. This result is very much consistent with the rate of 27.27% determined in this study.…”
Section: Discussionmentioning
confidence: 99%